Increase of neurofilament-H protein in sensory neurons in antiretroviral neuropathy: Evidence for a neuroprotective response mediated by the RNA-binding protein HuD. (September 2016) - Sanna, M.D.; Peroni, D.; Mello, T.; Ghelardini, C.; Quattrone, A.; Galeotti, N.
Graphical abstract: Abstract: Nucleoside reverse transcriptase inhibitors (NRTIs) are key components of HIV/AIDS treatment to reduce viral load. However, antiretroviral toxic neuropathy has become a common peripheral neuropathy among HIV/AIDS patients leading to discontinuation of antiretroviral therapy, for which the underlying pathogenesis is uncertain. This study examines the role of neurofilament (NF) proteins in the spinal dorsal horn, DRG and sciatic nerve after NRTI neurotoxicity in mice treated with zalcitabine (2′, 3′-dideoxycitidine; ddC). ddC administration up-regulated NF-M and pNF-H proteins with no effect on NF-L. The increase of pNF-H levels was counteracted by the silencing of HuD, an RNA binding protein involved in neuronal development and differentiation. Sciatic nerve sections of ddC exposed mice showed an increased axonal caliber, concomitantly to a pNF-H up-regulation. Both events were prevented by HuD silencing. pNF-H and HuD colocalize in DRG and spinal dorsal horn axons. However, the capability of HuD to bind NF mRNA was not demonstrated, indicating the presence of an indirect mechanism of control of NF expression by HuD. RNA immunoprecipitation experiments showed the capability of HuD to bind the BDNF mRNA and the administration of an anti-BDNF antibody prevented pNF-H increase. These data indicate the presence of a HuD – BDNF – NF-H pathway activated as a regenerative response to the axonal damage induced by ddC treatment to counteract the antiretroviral neurotoxicity. Since analgesics clinically used to treat neuropathic pain are ineffective on antiretroviral neuropathy, a neuroregenerative strategy might represent a new therapeutic opportunity to counteract neurotoxicity and avoid discontinuation or abandon of NRTI therapy.